Entrepreneurship as a Mobility Process - Sørensen, Jesper B.; Sharkey, Amanda J. (American Sociological Review, 2014)
We advance a theory of how organizational characteristics, in particular the structure of opportunity within organizations, shape the decision to become an entrepreneur. Established organizations play an important yet understudied role in the entrepreneurial process, because they shape the environment within which individuals may choose to enter self-employment. Yet, despite the fact that sociologists have long recognized that inequality within organizations plays an important role in career attainment and mobility, we lack an understanding of how it shapes the pursuit of entrepreneurial opportunities. We develop a formal model in which entrepreneurial choice is driven by differences in the arrival rate of various types of advancement opportunities. Entrepreneurship then arises as a result of matching processes between workers and employers, as well as the features of opportunity structures in paid employment. Analyses using Danish census data provide support for empirical implications derived from the model.